Antitumor Drug Delivery Modulated by A Polymeric Micelle with an Upper Critical Solution Temperature1. Issue 10 (28th January 2015) - Li, Weishuo; Huang, Liwen; Ying, Xiaoying; Jian, You; Hong, Yuan; Hu, Fuqiang; Du, Yongzhong
Abstract Thermally sensitive polymeric nanocarriers were developed to optimize the release profile of encapsulated compounds to improve treatment efficiency. However, when referring to thermally sensitive polymeric nanocarriers, this usually means systems fabricated from lower critical solution temperature (LCST) polymers, which have been intensively studied. To extend the field of thermally sensitive polymeric nanocarriers, we for the first time fabricated a polymeric drug delivery system having an upper critical solution temperature (UCST) of 43 °C based on an amphiphilic polymer poly(AAm‐co‐AN)‐g‐PEG. The resulting polymeric micelles could effectively encapsulate doxorubicin and exhibited thermally sensitive drug release both in vitro and in vivo. A drastically improved anticancer efficiency (IC50 decreased from 4.6 to 1.6 μg mL−1, tumor inhibition rate increased from 55.6 % to 92.8 %) was observed. These results suggest that UCST‐based drug delivery can be an alternative to thermally sensitive LCST‐based drug delivery systems for an enhanced antitumor efficiency.